Decongestive treatment adjustments in heart failure patients remotely monitored with a multiparametric implantable defibrillators algorithm. Issue 6 (3rd May 2022) - Guerra, Federico; D'Onofrio, Antonio; De Ruvo, Ermenegildo; Manzo, Michele; Santini, Luca; Giubilato, Giovanna; La Greca, Carmelo; Petracci, Barbara; Stronati, Giulia; Bianchi, Valter; Martino, Annamaria; Franculli, Fabio; et al.
Abstract: Aims: HeartLogic algorithm combines data from multiple implantable defibrillators (ICD)‐based sensors to predict impending heart failure (HF) decompensation. A treatment protocol to manage algorithm alerts is not yet known, although decongestive treatment adjustments are the most frequent alert‐triggered actions reported in clinical practice. We describe the implementation of HeartLogic for remote monitoring of HF patients, and we evaluate the approach to diuretic dosing and timing of the intervention in patients with device alerts. Methods: The algorithm was activated in 229 ICD patients at eight centers. The median follow‐up was 17 months (25th–75th percentile: 11–24). Remote data reviews and patient phone contacts were undertaken at the time of HeartLogic alerts, to assess the patient's status and to prevent HF worsening. We analyzed alert‐triggered augmented HF treatments, consisting of isolated increases in diuretics dosage. Results: We reported 242 alerts (0.8 alerts/patient‐year) in 123 patients, 137 (56%) alerts triggered clinical actions to treat HF. The HeartLogic index decreased after the 56 actions consisting of diuretics increase. Specifically, alerts resolved more quickly when the increases in dosing of diuretics were early rather than late: 28 days versus 62 days, p < .001. The need of hospitalization for further treatments to resolve the alert condition was associated with higher HeartLogic index values on the day of the diuretics increase (odds ratio: 1.11, 95% CI: 1.02–1.20, p = .013) and with late interventions (odds ratio: 5.11, 95% CI: 1.09–24.48, p = .041). No complications were reported after drug adjustments. Conclusions: Decongestive treatment adjustments triggered by alerts seem safe and effective. The early use of decongestive treatment and the use of high doses of diuretics seem to be associated with more favorable outcomes.